Design model of heavy-duty radial bearing running on micropolar grease with account of its viscosity-temperature characteristics - Kamill S. Akhverdiev; Elena O. Lagunova; Konstantin S. Solop (Advanced Engineering Research, 2016)
The study objective is to develop a method for calculating the plain journal bearing with an adapted profile of the bearing surface operating on the micropolar lubrication. Furthermore, it is assumed that the micropolar fluid viscosity characteristics are temperature dependent. Partial filling of the front gap with lubricant (i.e. availability of a free surface) is considered. Except regular dimensionless parameters of Newtonian fluid theory, other options for micropolar liquid are introduced, namely the interaction of N and N1 parameters characterizing the dependence on the size of the grease molecules. The numerical analysis shows that with the heat parameter ( К ) increment, the carrying capacity of the bearing decreases. With the increment of the parameters and characterizing the adapted profile of the bearing surface, the bearing capacity increases. At the parameter point of =0.5, maximum load capacity is achieved. At the bearing capacity value tends to the corresponding value for the case of Newtonian lubricant